## A community for students. Sign up today

Here's the question you clicked on:

## Shannon20150 2 years ago Factor the four-term polynomial. mn - 15 + 3m - 5n (m + 3)(n - 5) (n - 3)(m - 5) (n + 3)(m - 5)

• This Question is Closed
1. Shannon20150

I think it is the 1st one

2. sauravshakya

Nope

3. Shannon20150

okay how do u do it

4. whpalmer4

You should multiply out each of those expressions...you need the practice!

5. whpalmer4

The 1st one: \[(m+3)(n-5) = mn -5m + 3n - 15\]

6. Shannon20150

wat

7. sauravshakya

Let (m+x) (n+y) = mn - 15 + 3m - 5n => mn+ym+xn+xy=mn-15+3m-5n

8. sauravshakya

U need to find x and y from there

9. whpalmer4

\[(a+b)(c+d) = a(c+d) + b(c+d) = ac + ad + bc + bd\] If you want to be clever, note that to get a +3m, you need to have a +3 multiply an m, and there's only one such equation.

10. sauravshakya

comparing coffecients gives: x=-5 and y=3

11. sauravshakya

so, (m+x) (n+y) = mn - 15 + 3m - 5n = (m-5)(n+3)

12. sauravshakya

got it

13. Shannon20150

so its the last one

14. sauravshakya

yep

15. Shannon20150

okay lol help me again please

#### Ask your own question

Sign Up
Find more explanations on OpenStudy
Privacy Policy